2019
DOI: 10.1001/jamaoto.2019.1465
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Testing for Indeterminate Thyroid Nodules—When the Rubber Meets the Road

Abstract: Association of malignancy prevalence with test properties and performance of the gene expression classifier in indeterminate thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Most recent versions of molecular tests such as Afirma GSC and ThyroSeq v3 claim higher benign call rates than we found with the RFNA for AUS/FLUS (6, 7). However, predictive values of molecular tests in real-world seem to be lower than anticipated (42,43,44,45). Here we provide realworld data on 3932 AUS/FLUS nodules with RFNA from 27 studies, showing that diagnostic surgery can be safely (NPV greater than 96%) avoided in nearly 50% of AUS/FLUS with benign cytology on RFNA.…”
Section: Discussionmentioning
confidence: 80%
“…Most recent versions of molecular tests such as Afirma GSC and ThyroSeq v3 claim higher benign call rates than we found with the RFNA for AUS/FLUS (6, 7). However, predictive values of molecular tests in real-world seem to be lower than anticipated (42,43,44,45). Here we provide realworld data on 3932 AUS/FLUS nodules with RFNA from 27 studies, showing that diagnostic surgery can be safely (NPV greater than 96%) avoided in nearly 50% of AUS/FLUS with benign cytology on RFNA.…”
Section: Discussionmentioning
confidence: 80%
“…Oftentimes, effectiveness underperforms efficacy when initial studies are found to not perfectly represent the patients and physicians who use a diagnostic test. This might be because of eligibility requirements to participate in early studies, differences in patient populations at academic centers compared with community practices, interobserver differences in cytologic and pathologic analysis of follicular-patterned lesions, or other unknown factors . Confirming this, a recent analysis found that the Afirma GEC appeared to have lower sensitivity and specificity in 19 studies compared with data in the initial industry-sponsored study …”
Section: Observationsmentioning
confidence: 98%
“…This supports Afirma's validated 94% or greater NPV, 2 which has allowed most Afirma benign nodules to undergo conservative clinical observation in lieu of costly and invasive diagnostic surgery. 3 The authors compare the relationship of benign call rate (BCR) and positive predictive value (PPV) in postmarketing studies with that predicted from validation to assess diagnostic performance generalizability. In validation, the BCR and PPV are appropriately measured in the same cohort of thyroid nodules that underwent surgical resection.…”
mentioning
confidence: 99%
“…4 Unresected Afirma GEC benign nodules are highly likely to be benign, as has been shown in numerous studies. 3…”
mentioning
confidence: 99%
See 1 more Smart Citation